Saving the world and other extreme sports - Patterson, James, 1947- (London : Headline, 2007)
The time has come for Max, Fang, Iggy, Nudge, Gasman, and Angel to face their ultimate enemy and, despite many obstacles, try to save the world from a sinister plan to re-engineer a select population into a scientifically superior master race.
Young Adult.
Young Adult
Keywords: Adventure and adventurers -- Juvenile fiction; Genetic engineering -- Juvenile fiction; Adventure and adventurers -- Fiction; Genetic engineering -- Fiction; Science fiction; Adventure fiction; Genetic engineering -- Fiction; Science fiction; Science fiction